Something Alien? The Limits of U.S. Influence in UK Campaigns. Issue 1 (2nd January 2017) - Wring, Dominic
Abstract : The campaign consulting business in the United States is the largest in the world and has had some success in globally exporting its expertise in terms of both personnel and technique. This paper reflects on the so-called "Americanization" of British elections and draws attention to some of the significant landmarks in the relationship between strategists in the two countries. The discussion does, however, identify the limitations of this idea as an organizing concept for understanding how election campaigning has developed in the United Kingdom.